2021
DOI: 10.21203/rs.3.rs-144596/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Probiotic Activities and Biosafety of Lactobacillus gasseri HHuMIN D

Abstract: Background Specific probiotic bacteria may have inhibitory effects against oral pathogens. Lactobacillus spp. have been researched worldwide and are used in probiotics, but due to difficulties with laboratory cultivation of and experimentation on oral microorganisms, there are few reports of Lactobacillus spp. being isolated from the oral cavity and tested against oral pathogens. This research aimed to determine the safety and inhibitory impacts of L. gasseri HHuMIN D as a potential oral probiotic with biothe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(101 reference statements)
1
1
0
Order By: Relevance
“…28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo, indicating that they can metabolize and produce bacteriostatic substances. In the case of excluding the influence of acid, the fermentation supernatant of LAB can also significantly inhibit the growth of H. pylori, indicating that in addition to the secretion of organic acids, it can also produce other antibacterial substances.…”
Section: Discussionsupporting
confidence: 81%
“…28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo, indicating that they can metabolize and produce bacteriostatic substances. In the case of excluding the influence of acid, the fermentation supernatant of LAB can also significantly inhibit the growth of H. pylori, indicating that in addition to the secretion of organic acids, it can also produce other antibacterial substances.…”
Section: Discussionsupporting
confidence: 81%
“…Probiotic characteristics; antimicrobial activity; innate immune responses in epithelial cells [131,132] Bacteremia [133] Lactobacillus gasseri Probiotic characteristics; used in food industry as supplements; inhibit increase in body weight and adipose tissue weight [134,135] Liver abscesses [136]…”
Section: Ligilactobacillus Salivariusmentioning
confidence: 99%